2013
DOI: 10.1016/j.jmatprotec.2013.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Fiber laser induced surface modification/manipulation of an ultrasonically consolidated metal matrix

Abstract: Ultrasonic Consolidation (UC) is a manufacturing technique based on the ultrasonic joining of a sequence of metal foils. It has been shown to be a suitable method for fiber embedment into metal matrices. However, integration of high volume fractions of fibers requires a method for accurate positioning and secure placement to maintain fiber layouts within the matrices. This paper investigates the use of a fiber laser for microchannel creation in UC samples to allow such fiber layout patterns. A secondary goal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
(28 reference statements)
0
17
0
Order By: Relevance
“…As detailed in Table 3, a higher gas pressure of 0.8 MPa decreased the width of the HAZ. It was suggested that a difference in surface tension between the channel boundaries and the center of the melt pool hindered a uni form distribution of the melt to both sides of the channel which has been discussed elsewhere [35]. Both, a higher gas pressure and a faster traverse speed, allow for less heat to be conducted into the material.…”
Section: Influence Of Multiple Laser Passes On the Microstruc Turementioning
confidence: 99%
See 1 more Smart Citation
“…As detailed in Table 3, a higher gas pressure of 0.8 MPa decreased the width of the HAZ. It was suggested that a difference in surface tension between the channel boundaries and the center of the melt pool hindered a uni form distribution of the melt to both sides of the channel which has been discussed elsewhere [35]. Both, a higher gas pressure and a faster traverse speed, allow for less heat to be conducted into the material.…”
Section: Influence Of Multiple Laser Passes On the Microstruc Turementioning
confidence: 99%
“…A Fiber laser allowed focusing the beam to narrow spot sizes which was necessary to achieve the desired channel width of 120/rm-150jtnn which was determined by the diameters of the intended future embedded fibers. A detailed analysis of the varied parameters on the channel/shoulder geometry has been shown elsewhere [35]. The beam quality factor of the fiber laser was M2 < 1.2.…”
Section: Laser Processingmentioning
confidence: 99%
“…This permits the reduction of the required amplitude, and thus the necessary matrix plastic flow [40]. Channels were created in the samples using fiber laser irradiation (Figure 10a).…”
Section: Embedding Processesmentioning
confidence: 99%
“…19 The channel production process has been described elsewhere. 20 The samples for the SPI 200 W fibre laser were processed using a power of 140 W, a speed of 275 mm/min and a nitrogen gas pressure of 0.6 MPa. The samples for the Trumpf TruFiber 300 W laser were processed using a power of 250 W, a traverse speed of 200 mm/min and an air gas pressure of 0.8 MPa.…”
Section: Channel Processingmentioning
confidence: 99%
“…This was due to the flow of the melt and has been previously discussed. 20 In order to explore the influences of the channel, one-sided shoulder and fibre orientation, which would possibly influence plastic flow behaviour and bond formation during UC, 8 samples containing channels perpendicular and parallel to the welding direction were considered. In Figure 4, both channel types are displayed.…”
Section: Channel Processingmentioning
confidence: 99%